Strategi Komunikasi Dakwah Ustadz Das'ad Latif di TikTok - Aziz Muhtar Yusuf; Arik Dwi Jayanto; Dewi Yunita Sari (IAIN PONOROGO, 2026)
This study examines the da'wah communication strategies of Ustadz Das'ad Latif on the TikTok platform (@dasadlatifofficial) in response to the growing development of short-video social media in Indonesia. Employing a descriptive qualitative approach through virtual ethnography, data were collected via participatory observation, content analysis, and digital interaction tracing during January–June 2025, with a data corpus of 2,100 videos and a purposive sample of 200 videos selected for in-depth analysis. The findings identify four integrated digital da'wah strategies: (1) message strategy, through the simplification of religious messages based on analogy and contextualization of contemporary issues; (2) presentation strategy, through visual consistency, code-mixing language use, and personal narrative techniques; (3) interactivity strategy, through participatory dialogue, video reply features, and live streaming sessions; and (4) algorithmic strategy, through hashtag optimization, consistent upload scheduling, and content duration adaptation. This study concludes that digital da'wah on TikTok is not merely a transfer of medium, but rather a comprehensive reconstruction of communication strategies adapted to the logic of digital platforms, thereby offering a significant contribution to the development of digital da'wah studies and contemporary Islamic communication in the social media era.